The Pathological Study of Suspected Swollen Head Syndrome in Broiler Chickens - Bambang Sutrisno; Sitarina Widyarini; R Wasito; Hastari Wuryastuty (Jurnal Sain Veteriner, 2013)
The  objective of this study was to determine the pathological lesions of the broiler chickens having the clinical signs that appeared to be the swollen head syndrome (SHS),  such as simetrically and bilaterally swollen periorbital areas. Eighteen broiler chickens were collected from three poultry farms of the three diffrerent areas, e.g. Kulonprogo, Sleman and Bantul at Special Province of Yogyakarta, respectively. Six of those broiler chickens were selected from each poultry farm consisted of three SHS- broiler chickens and three non SHS-broiler chickens. All of broiler chickens were necropsied, observed anatomic patologic lesions, and then the organs of interest were processed and stained routinely with hematoxylin and eosin for histopathologic examination. Subcutaneus edema and cellulitis were found in the frontal and occipital skin. Based on the histopathological examination, purulent and granulomatous cellulitis and lymphocytic perivasculitis, and subcutaneus edema were found in the frontal and occipital skin. Other lesions, such as: necrotic, lymphocytic sinusitis, tracheitis and pneumonia accompanied by atrophy of mucosal glands were also present. It is concluded that the pathological lesions of SHS in the broiler chickens were found not only in the frontal and occipatal skin, but also in both lower and upper respiratory tracts.